SPITZER ULTRA FAINT SURVEY PROGRAM (SURFS UP). II. IRAC-DETECTED LYMAN-BREAK GALAXIES AT 6 z 10 BEHIND STRONG-LENSING CLUSTERS - Huang, Kuang-Han; Brada, Maruša; Lemaux, Brian C.; Ryan, Jr, R. E.; Hoag, Austin; Castellano, Marco; Amorín, Ricardo; Fontana, Adriano; Brammer, Gabriel B.; Cain, Benjamin; Lubin, L. M.; Merlin, Emiliano; et al. (The Astrophysical journal, 2016)
ABSTRACT We study the stellar population properties of the IRAC-detected 6 z 10 galaxy candidates from the Spitzer UltRa Faint SUrvey Program. Using the Lyman Break selection technique, we find a total of 17 galaxy candidates at 6 z 10 from Hubble Space Telescope images (including the full-depth images from the Hubble Frontier Fields program for MACS 1149 and MACS 0717) that have detections at signal-to-noise ratios ≥ 3 in at least one of the IRAC 3.6 and 4.5 m channels. According to the best mass models available for the surveyed galaxy clusters, these IRAC-detected galaxy candidates are magnified by factors of ∼1.2-5.5. Due to the magnification of the foreground galaxy clusters, the rest-frame UV absolute magnitudes M1600 are between −21.2 and −18.9 mag, while their intrinsic stellar masses are between 2 × 108M and 2.9 × 109M . We identify two Ly emitters in our sample from the Keck DEIMOS spectra, one at zLy = 6.76 (in RXJ 1347) and one at zLy = 6.32 (in MACS 0454). We find that 4 out of 17 z 6 galaxy candidates are favored by z 1 solutions when IRAC fluxes are included in photometric redshift fitting. We also show that IRAC [3.6]-[4.5] color, when combined with photometric redshift, can be used to identify galaxies which likely have strong nebular emission lines or obscured active galactic nucleus contributions within certain redshift windows.